2021
DOI: 10.5194/essd-2021-235
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing national greenhouse gas budgets reported in UNFCCC inventories against atmospheric inversions

Abstract: Abstract. In support of the Global Stocktake of the Paris Agreement on Climate change, this study presents a comprehensive framework to process the results of atmospheric inversions in order to make them suitable for evaluating UNFCCC national inventories of land-use carbon dioxide (CO2) emissions and removals, corresponding to the Land Use, Land Use Change and Forestry and waste sectors. We also deduced anthropogenic methane (CH4) emissions regrouped into fossil and agriculture and waste emissions, and anthro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 83 publications
(121 reference statements)
8
37
0
Order By: Relevance
“…Except for Russia and Indonesia, these bring emission estimates in closer agreement with other top-down studies (e.g. Deng et al, 2021).…”
Section: Global Emission Estimatessupporting
confidence: 90%
See 1 more Smart Citation
“…Except for Russia and Indonesia, these bring emission estimates in closer agreement with other top-down studies (e.g. Deng et al, 2021).…”
Section: Global Emission Estimatessupporting
confidence: 90%
“…Using prior emission maps, we distributed total posterior emissions into 6 sector specific categories; energy, agriculture, waste, other anthropogenic, wetlands and fires. In agreement with multiple inverse studies (Deng et al, 2021) most of the overestimated emissions from China are found to originate from the energy sector (1.9 Tg yr -1 ) and specifically from the coal mining regions of Outer Mongolia, Shaanxi and Shanxi. Relative to the prior, posterior emissions are reduced from India (-3.0%) and Pakistan (-1.1%), increased from Brazil (+1.3%) and less than 1% different for the USA (0.5%), Indonesia (0.3%), EU27+UK (+0.1%) and Russia (-0.7%).…”
Section: Global Emission Estimatessupporting
confidence: 88%
“…Figure 9 further highlights the lack of recent official national emissions inventories for many non-Annex I countries. The BURs are also associated with less stringent reporting requirements in terms of sector, gas, and time coverage (Deng et al, 2021;Gütschow et al, 2016). This highlights the important role of global inventories such as EDGAR, CEDS, PRIMAP-hist, FAOSTAT, or those from IEA or BP among others that are equally as comprehensive in scope as those from Annex I countries.…”
Section: Discussionmentioning
confidence: 99%
“…GHG emissions reporting under the United Nations Framework Convention on Climate Change (UNFCCC) provides reliable, comprehensive, and up-to-date statistics for Annex I countries across all major GHGs. Non-Annex I countries -except the least devel-oped countries and small island states for which this is not mandatory -provide GHG emissions inventory information through biennial update reports (BURs) but with much less stringent reporting requirements in terms of sector, gas, and time coverage (Deng et al, 2021;Gütschow et al, 2016). As a result, many still lack a well-developed statistical infrastructure to provide detailed reports (Janssens-Maenhout et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, societal momentum to reduce CO2 emissions has strengthened globally in response to the 1.5°C /2.0°C target of the Paris agreement, and CO2 flux data from inverse analyses are becoming an important source of information used to independently evaluate national inventories. The latest studies by Chevalllier (2021) and Deng et al (2021) compared inversion fluxes with national inventories based on agriculture, forestry, and other land use changes (LUCs). However, they used data from global-scale inversions with horizontal resolutions generally around hundreds of kilometers.…”
Section: Introductionmentioning
confidence: 99%